Secondhand Smoke exposure and risk of Obstructive Sleep Apnea in Children. (March 2020) - Subramanyam, Rajeev; Tapia, Ignacio E.; Zhang, Bingqing; Mensinger, Janell L.; Garcia-Marcinkiewicz, Annery; Jablonka, Denis H.; Gálvez, Jorge A; Arnez, Karina; Schnoll, Robert
Abstract: Objectives: Obstructive sleep apnea (OSA) has a prevalence of 4% in children. Few studies have explored the role of secondhand smoke (SHS) on OSA severity and have shown contradicting results. Most studies have focused on the effect of SHS on snoring. This study explored the association of SHS exposure and OSA severity in children aged 3–18 years. Methods: This is a retrospective single center IRB-approved study. Electronic Medical Records (EMR) were queried between 1/24/2015 and 1/24/2018 to obtain data on SHS exposure with standard questionnaires from perioperative database. SHS was analyzed as a binary variable and OSA was measured using obstructive apnea hypopnea index (OAHI) from polysomnography (PSG) as a continuous variable. Analyses were done on all children and in those with severe OSA (OAHI≥10/h) as a subgroup. Results: EMR query yielded 101, 884 children of whom 3776 had PSG. Limiting baseline PSG in 3–18-year-old and reliable information on SHS yielded 167 analyzable children of whom 70 had severe OSA. Children exposed to SHS had significantly more public insurance than non-exposed (p < 0.0001). Among children with severe OSA, median OAHI was significantly higher in SHS exposed compared to non-exposed (29.0vs.19.5, p = 0.04), but not across all children. In multivariable analysis SHS exposure increased OAHI by 48% in severe OSA subgroup (95%CI: 8%–102%; p = 0.01) when adjusted for race, body mass index, and adjusted household income. Conclusion: Children aged 3–18 years with severe OSA who were exposed to SHS were found to have 1.48 increase in odds of OAHI than those without SHS exposure. Results could be limited by retrospective nature of study and EMR tools.